I’JAZ AL-ILMI FIL HADIS: Tinjauan Terhadap Wudu dan Pengaruhnya Bagi Kesehatan - Manaf, Abdul; Novera, Melia (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2022)
Every Shari'a that Allah swt has set for his servants will certainly have an impact on his servants who do it perfectly. The impact is not only related to the reward he gets as a provision for the afterlife, but also has a positive impact that can be felt directly when in the world. However, some of us are still not fully aware of this. Therefore, through a scientific approach, scholars and researchers try to uncover the secrets contained in the practices prescribed by the Shari'a, including ablution. Wudu as part of Islamic law which is performed at least five times a day, is not only a requirement for the validity of a worship. Based on research conducted by people who are struggling in the world of health, it was found that ablution can have a very good effect on body health. By doing ablution, it means that someone has cleaned the open part of the body, where the part is the most contaminated place for bacteria, improves blood flow, and gives peace of mind. In the Islamic world, the compatibility between the news conveyed by the Qur'an or the Prophet's Hadith and scientific facts proven by modern science is called I'jaz Ilmi. Understanding wudu through the I'jaz Ilmi approach can lead to seriousness in its practice, improve the quality of faith because it sees scientific facts, and as a response to the thoughts of people who doubt the truth of the Prophet Muhammad's message